Rural Urban Differentials of Treatment Seeking Behavior for Acute Respiratory Infection Among Children in Puducherry - Majumdar, Anindo; Premarajan, K C; Ganesh, Kumar S; Veerakumar, A M; Ramaswamy, Gomathi (National Journal of Community Medicine, 2014)
Purpose: To explore the rural-urban differentials with respect to treatment seeking behaviour and cost incurred for Acute Respiratory Infection (ARI) among under-five children. Methodology: A community-based cross-sectional study was conducted in Puducherry among 270 under-five children. Data on treatment seeking behaviour and cost incurred was collected from the parents using a semi-structured questionnaire. Results: The perceived severity of ARI episode was significantly higher among rural areas compared to urban (p=0.04). For consultation, majority preferred the government sector (63%) in rural and private sector in urban areas (51.2%). Main reasons for preferring type of consultation were proximity (61.1%) and trust (51.2%) in rural and urban areas respectively. Rural parents were significantly less satisfied with outside consultation (p=0.003). Home remedies were preferred by 17.9% and 10% parents in rural and urban areas respectively. Median direct cost incurred in both areas was Rs 250. Conclusion: Differences in treatment seeking behaviour should be kept in mind while designing interventions.